PELATIHAN PENYUSUNAN MODEL PEMBELAJARAN RENANG BERBASIS NILAI-NILAI MORAL RELIGIUS BAGI MAHASISWA FIK UNY - Sismadiyanto, Sismadiyanto; Susanto, Ermawan; Subagyo, Subagyo (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2010)
This training aims at giving preview in the arrangement of swimming teaching model based on religious moral values for students of FIK UNY. There  are  two  approaches  for  activities  method.  First  is  theoretical approach which consists of material presentation, discussion, and question answer. Second one is practical approach which consists of mastering the swimming basic technique, class management based on religious moral values, water games, etc. Each of approaches then was evaluated using  swimming teaching program based on religious moral values. The material presentation focuses on: theoretical and practical material about swimming basic skill, swimming rules, basic safety water, and swimming teaching model based on religious moral values. The indication of training successfulness could be seen from the high motivation of participants in following it and also from the new science and skill about swimming learning model based on religious moral values that was gotten. The program of people service was going well and followed by 31 of participants. Based on result discussion that was presented then there are some high light points: (1) There are lots of students voices that hoping a special class in swimming subject which separates male and female students, (2) They also want to use swimsuit that can close over the body, (3) there is a tension from female students who wear veil then she leave out it because of swimming rule about cloth manner in swimming class, (4) time for swimming class is just same with public visitors who also use same facilities of pool so then it could be like a public show for them, (5) It should be a female teacher for female students and a male teacher for males